Contribution of MSMES To The Economy of Cirebon Regency In The Covid-19 Pandemic - Pahrul Fauzi; Syaeful Bakhri; Isman Julian (IAIN Syekh Nurjati Cirebon, 2022)
Micro, small and medium enterprises or SMEs have a role that is very important in advancing the Indonesian economy, especially the economy in areas such as Cirebon Regency which is a Trade Regency. The existence of MSMEs in the Cirebon Regency for contributions or contributions to GRDP during the current Covid-19 pandemic condition is certainly something that must be maintained. This study aims to map the industrial sector development centers in Cirebon Regency during the Covid-19 Pandemic by using a quantitative descriptive approach and using the Location Quotient (LQ) analysis tool as an analytical tool. Based on the results of the analysis, it can be seen that as a result of the Covid-19 pandemic, Cirebon Regency experienced an economic shift with increasing economic sectors, both secondary and tertiary. Then several economic sectors such as services and the agricultural, forestry, and livestock sectors contributed significantly and experienced positive growth. There are superior commodities that grow and develop well, such as the rattan and furniture industry, then processed food and batik. Meanwhile, the results of the analysis of the potential for small and medium industry centers (IKM) that are recommended to be superior SMEs are the woven bamboo IKM center, the pindang fish IKM center and the tempe and tofu IKM center